2021
DOI: 10.1098/rstb.2020.0247
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal auditory learning in avian vocal learners and non-learners

Abstract: Understanding when learning begins is critical for identifying the factors that shape both the developmental course and the function of information acquisition. Until recently, sufficient development of the neural substrates for any sort of vocal learning to begin in songbirds was thought to be reached well after hatching. New research shows that embryonic gene activation and the outcome of vocal learning can be modulated by sound exposure in ovo . We tested whether avian embryos across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Two more potential hypotheses for SOTN are that it is used for song learning and parent identification (reviewed in Haff et al 2015). Traditionally, song learning in birds is thought to occur during a critical period during the late nestling and fledgling stages (Marler and Peters 1981), but growing evidence indicates that developing bird embryos respond to and are shaped by their prenatal acoustic environment (e.g., Katsis et al 2018, Rivera et al 2018, Colombelli-Négrel et al 2021). We found that SOTN rate was significantly higher during the egg stage; however, the role of acoustic signals during the egg stage of mockingbirds remains unstudied and our results suggest this needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two more potential hypotheses for SOTN are that it is used for song learning and parent identification (reviewed in Haff et al 2015). Traditionally, song learning in birds is thought to occur during a critical period during the late nestling and fledgling stages (Marler and Peters 1981), but growing evidence indicates that developing bird embryos respond to and are shaped by their prenatal acoustic environment (e.g., Katsis et al 2018, Rivera et al 2018, Colombelli-Négrel et al 2021). We found that SOTN rate was significantly higher during the egg stage; however, the role of acoustic signals during the egg stage of mockingbirds remains unstudied and our results suggest this needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Vocal learning was traditionally thought to occur beginning in the fledgling stage (Marler and Peters 1981); however, a growing body of literature demonstrates that vocal learning begins while developing birds are still in the egg (e.g., Katsis et al 2018, Rivera et al 2018, Colombelli-Négrel et al 2021). We, therefore, predicted that if SOTN functions in vocal learning, then SOTN should occur during both the egg and nestling stages (see Coordination of Parental Care above for details of analysis).…”
Section: Vocal Learningmentioning
confidence: 99%
“…If vocal learning were present in the ancestors of birds, one might imagine communities of singing dinosaurs using learned song to defend their territory and to woo their mates. 237 Recent research has suggested that, in some species, this process may even begin in ovo, before hatching (Colombelli-Négrel et al, 2021).…”
Section: The Acquisition Of Learned Bird-songmentioning
confidence: 99%
“…It is often assumed that the sensitive period for vocal learning in birds commences sometime after hatching. However, as the paper by Colombelli-Negrel et al [23] makes clear, embryos of various species can perceive and respond to sounds in ovo. The species in the study are few, but highly varied, including a Darwin's finch, two fairy wrens, a penguin and a quail.…”
Section: Vocal Learning Early In Lifementioning
confidence: 99%